Clinical Study of Different Modes of Non-invasive Ventilation Treatment in Preterm Infants With Respiratory Distress Syndrome After Extubation - Ding, Fei; Zhang, Jingling; Zhang, Wenya; Zhao, Qian; Cheng, Zimei; Wang, Yang; Bo, Tao; Wu, Hui (Frontiers in Pediatrics, 2020)
Objective: This study aimed to investigate the clinical efficacy and safety of different non-invasive respiratory support methods in preterm infants with respiratory distress syndrome (RDS) after extubation. Methods: From Oct 2017 to Oct 2018, 120 preterm infants were recruited from the NICUs of three hospitals. They were diagnosed with RDS and required mechanical ventilation. After extubation from mechanical ventilation, these infants were divided into NCPAP group, SNIPPV group and SNIPPV + NCPAP group. The time of noninvasive ventilation, reintubation rate within 72 h, success rate of noninvasive ventilation within one week, duration of oxygen therapy, hospital stay and incidence of complications were recorded and compared. Results: Compared with the NCPAP group, the SNIPPV group and the SNIPPV + NCPAP group had significantly higher rate of successful extubation and removal from noninvasive ventilation within one week (P<0.05). There were no significant differences among three groups in the time of noninvasive ventilation, time of oxygen therapy, hospital stay or incidence of complications (P>0.05). Conclusion: SNIPPV + NCPAP after mechanical ventilation is a relatively safe and effective ventilation strategy for preterm infants with severe RDS. The use of NCPAP facilitates the turnover of SNIPPV ventilators in developing countries.